2022
DOI: 10.1177/21582440221102444
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Assessment of Safe and Risky Driving Behaviors: Pedestrians Versus Drivers

Abstract: Interactions between pedestrians and drivers are an important traffic safety issue. Psycho-social factors such as thoughts, perceptions and attitudes toward other people can be reliable predictors of riskier or safer behaviors among road users. The aim of this study was to assess how frequently participants perceive that drivers perform safe and risky road behaviors through drivers’ self-reported behavior and pedestrians and other drivers’ external perceptions. The results show that pedestrians assess the road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Sergio et al [ 8 ] presented the Walking Behavior Questionnaire (WBQ), which identifies traffic violations as an issue of road user safety, to thoroughly describe the validation of an instrument for measuring the walking risky and positive behavior on the road, using the Walking Behavior Questionnaire. Francisco et al [ 9 ] evaluated the differences between safe and dangerous driving behaviors from the perspectives of pedestrians and drivers, and the results showed that pedestrians had a very negative evaluation of the driver's road behavior. At the same time, drivers believe that their own behavior is more appropriate than the behavior of other drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Sergio et al [ 8 ] presented the Walking Behavior Questionnaire (WBQ), which identifies traffic violations as an issue of road user safety, to thoroughly describe the validation of an instrument for measuring the walking risky and positive behavior on the road, using the Walking Behavior Questionnaire. Francisco et al [ 9 ] evaluated the differences between safe and dangerous driving behaviors from the perspectives of pedestrians and drivers, and the results showed that pedestrians had a very negative evaluation of the driver's road behavior. At the same time, drivers believe that their own behavior is more appropriate than the behavior of other drivers.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the quality of many of the skills should be measured with reliable instruments for vulnerable people [ 10 , 11 ]. These skills are also necessary as safe driving performance decreases [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], which is reflected in crash rates and their severity. The involvement of older people in fatal accidents is estimated to increase by 155% by 2030, accounting for 54% of the total projected increase in the number of total fatal accidents [ 19 ].…”
Section: Introductionmentioning
confidence: 99%